Using Swarm Intelligence Algorithms for Optimization in IoT Applications - Roshanzamir, Mohamad; Nematollahi, Mohammad Ali; Darbandy, Mohammad Tayarani; Roshanzamir, Mahdi; Alizadehsani, Roohallah; Shoeibi, Afshin; Ahmadian, Davood (2022 IEEE 10th Jubilee International Conference on Computational Cybernetics and Cyber-Medical Systems (ICCC), 2022)
Internet of Things (IoT) is considered as the next industrial revolution in the years ahead. Many devices will have been connected to the Internet and more and more devices were added to them. The number of these types of devices is increased rapidly. So, management of them needs advanced technologies. Optimization of different problems in IoT is an essential subject of many researches and Swarm Intelligence algorithms (SI) are one of the most successful methods in this field. They were inspired by the collective behavior of simple creatures which communicate directly and indirectly with each other. Although they are considered as simple agents, their collective behavior is smart. They can overcome most problems in their life using collective behavior. In this research, we investigated some of the most common optimization problems in IoT and the SI algorithms which are used to solve them.